2020
DOI: 10.1785/0220190378
|View full text |Cite
|
Sign up to set email alerts
|

Cascading Partial Rupture of the Flores Thrust during the 2018 Lombok Earthquake Sequence, Indonesia

Abstract: A series of four Mw>6 earthquakes struck the northern region of Lombok, eastern Indonesia, in a span of three weeks from late July to mid-August 2018. The series was thought to be associated with the Flores thrust, but the exact mechanism causing the unusual earthquake series has remained elusive. Our Interferometric Synthetic Aperture Radar analysis, combined with insights from seismology, indicates that the events originated at different hypocenter depths with differing fault geometries, which may exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…We did not use all the possible InSAR images [such as in Salman et al, (7)], but select one ascending (ALOS-2) and one descending (Sentinel-1) InSAR image for each earthquake, and because these satellites have similar-looking angles to the ground, ascending/descending images from ALOS-2 is similar to that from Sentinel-1 [see more details in Salman et al, (7)]. For the slip model inversion, derived displacement measurements were downsampled using the quadtree structures (37).…”
Section: Insar Data For the Sequencementioning
confidence: 99%
“…We did not use all the possible InSAR images [such as in Salman et al, (7)], but select one ascending (ALOS-2) and one descending (Sentinel-1) InSAR image for each earthquake, and because these satellites have similar-looking angles to the ground, ascending/descending images from ALOS-2 is similar to that from Sentinel-1 [see more details in Salman et al, (7)]. For the slip model inversion, derived displacement measurements were downsampled using the quadtree structures (37).…”
Section: Insar Data For the Sequencementioning
confidence: 99%
“…A relationship between faulting and volcanic activity was observed for the 2018 Lombok earthquake sequence, which generated four >Mw 6 events between 28 th July to 19 th August. These earthquakes did not occur offshore on the northern frontal thrust of the Flores Thrust, but instead involved slip along the deeper part of the fault and associated imbricate thrusts beneath Lombok, to the north of the active Rinjani volcano (Salman et al, 2020;Yang et al, 2020;Lythgoe et al, 2021). While these earthquakes were not 105 directly caused by volcanic activity, the presence of the volcano constrained the earthquake distribution by elevating the downdip limit of the seismogenic zone in the crust (Lythgoe et al, 2021).…”
Section: Seismicity Of the Flores Thrustmentioning
confidence: 99%
“…The significant earthquakes that occurred several times were indicated as the result of segmentation ruptures formed before the occurrence of a strong earthquake (Wang et al, 2020;Sasmi et al, 2020). Salman et al (2020) using InSAR data also explained that the significant earthquake sequences came from different hypocenters, and formed a rupture of a thrust fault that tilted to the south. This earthquake sequence might trigger secondary disasters such as landslides (Ferrario, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This earthquake sequence might trigger secondary disasters such as landslides (Ferrario, 2019). In addition, it is suggested that the 2018 Lombok earthquake might cause a volumetric expansion in the shallow magma plumbing system at Rinjani volcano, which might affect the volcanic activity in the future (Salman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation